Evaluation of changes to work patterns in multidisciplinary cancer team meetings due to the COVID‐19 pandemic: A national mixed‐method survey study. (17th January 2023) - Soukup, Tayana; Winters, David; Chua, Kia‐Chong; Rowland, Philip; Moneke, Jacqueline; Skolarus, Ted A.; Bharathan, Rasiah; Harling, Leanne; Bali, Anish; Asher, Viren; Gandamihardja, Tasha; Sevdalis, Nick; et al.
Abstract: Background: It is not well understood the overall changes that multidisciplinary teams (MDTs) have had to make in response to the COVID‐19 pandemic, nor the impact that such changes, in addition to the other challenges faced by MDTs, have had on decision‐making, communication, or participation in the context of MDT meetings specifically. Methods: This was a mixed method, prospective cross‐sectional survey study taking place in the United Kingdom between September 2020 and August 2021. Results: The participants were 423 MDT members. Qualitative findings revealed hybrid working and possibility of virtual attendance as the change introduced because of COVID‐19 that MDTs would like to maintain. However, IT‐related issues, slower meetings, longer lists and delays were identified as common with improving of the IT infrastructure necessary going forward. In contrast, virtual meetings and increased attendance/availability of clinicians were highlighted as the positive outcomes resulting from the change. Quantitative findings showed significant improvement from before COVID‐19 for MDT meeting organisation and logistics ( M  = 45, SD = 20) compared to the access ( M  = 50, SD = 12, t (390) = 5.028, p  = 0.001), case discussions ( M  = 50, SD = 14, t (373) = −5.104, p  = 0.001), and patient representation ( M  = 50, SD = 12, t (382) = −4.537, p  = 0.001) at MDT meetings. Discussion: Our study explored the perception of change since COVID‐19 among cancer MDTs using mixed methods. While hybrid working was preferred, challenges exist. Significant improvements in the meeting organisation and logistics were reported. Although we found no significant perceived worsening across the four domains investigated, there was an indication in this direction for the case discussions warranting further 'live' assessments of MDT meetings. Abstract : Multidisciplinary teams (MDTs) are a gold standard in cancer care. Qualitative findings revealed hybrid working and possibility of virtual attendance as the change introduced because of COVID‐19 that MDTs would like to maintain. IT‐related issues, slower meetings, longer lists and delays were reported as common with further improvement of the IT infrastructure critical.